Complexity and Relative Complexity in Generative Grammar - Newmeyer, Frederick J. (Frontiers in Communication, 2021)
The notions of ‘complexity’ and its antonym ‘simplicity’ have played an important role in the history of generative grammar. However, these terms have been used in different ways. There have been discussions about whether the raw data is complex (or not), about whether a particular theory is complex (or not), and about whether a particular analysis is complex (or not). This article both sorts out the various uses of these terms in the history of generative grammar and demonstrates that motivations have changed over time for whether a complex theory or a simple theory is more desirable. The article concludes with a discussion of the issue of relative complexity in generative grammar, that is, whether the theory embodies the possibility that a grammar of one language can be more or less complex than the grammar of another.